Politician personality, Machiavellianism, and political skill as predictors of performance ratings in political roles. Issue 2 (9th October 2013) - Silvester, Jo; Wyatt, Madeleine; Randall, Ray
<x xml:space="preserve">Abstract</x> This study conceptualizes politicians as political workers. It describes a multimethod study with two aims: (1) to determine whether politicians share a latent mental model of performance in political roles and (2) to test hypothesized relationships between politician self‐rated characteristics (i.e., extroversion, neuroticism, conscientiousness, Machiavellianism, and political skill) and received performance ratings from political colleagues and officers. Two hundred and thirty‐one local politicians provided self‐ratings on a political performance questionnaire developed following a role analysis, and standardized measures of personality. One hundred and eighty‐five also received performance ratings from colleagues (n = 749) and officers (n = 729). Exploratory and confirmatory factor analyses of self‐ and received performance ratings revealed five latent factors: Resilience (RS), Politicking, Analytical Skills (AS), Representing People, and Relating to Others. Regression analyses found that neuroticism and conscientiousness contribute to received ratings of RS, and neuroticism contributes to received ratings of AS. Practitioner points As political roles require political work, we argue there is potential to use research and practice from I/O psychology to improve politician performance. The existence of shared latent constructs of performance provides a basis for differentiated criterion assessment in political roles. Evidence that individual differences contribute to political performance can be used to shape support activities for individuals in elected roles.